Severe myocarditis as a cause of the formation of cardiorenal syndrome in a patient with refractory rheumatoid arthritis - Z. Yu. Mutovina; A. V. Gordeev; I. V. Rozanova; E. A. Galushko (Научно-практическая ревматология, 2022)
According to modern concepts, myocarditis is an inflammatory disease of the myocardium, diagnosed on the basis of generally accepted histological, immunological, immunohistochemical criteria. Previously, most researchers believed that the most common cardiac extra-articular manifestation of rheumatoid arthritis (RA) is pericarditis. In the last decade, using magnetic resonance imaging (MRI) of the heart, it turned out that myocarditis in patients with rheumatoid arthritis is not a rare manifestation of the disease. Recently, there is increasing evidence that inflammatory cytokines in RA can also directly cause chronic myocardial damage, further contributing to the development of chronic heart failure (CHF). In our clinical case, myocarditis developed in a patient with active refractory rheumatoid arthritis. The myocardial lesion in the patient was characterized by pronounced echocardiographic signs of restrictive cardiomyopathy, a significant decrease in the ejection fraction with the development of heart failure, various rhythm disturbances in combination with acute renal dysfunction, which led to the formation of cardiorenal syndrome (CRS). Complete regression of myocarditis and cattle occurred precisely against the background of effective treatment of refractory rheumatoid arthritis (RA) with basic antirheumatic drugs and the successful use of biological therapy.